Old-Age Support in Developing Countries: Labor Supply, Intergenerational Transfers and Living Arrangements - Lisa Cameron; Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2001)
Without broad-based public pension schemes, the majority of the elderly in developing countries are left to rely on their own current and accumulated earnings and support from children as means of old-age support. We develop a cooperative bargaining model that allows us to jointly estimate the determinants of coresidency, financial transfers from non-coresiding children, and the labor-supply of elderly Indonesians. We find that many Indonesians, especially men, continue to work well into old age even if they are living with their adult children. There is little evidence that transfers are a substitute for the income support provided by the elderly parent?s own labor supply. Transfers are associated with a decline in hours of work only for noncoresiding mothers. Furthermore, transfers are not strongly related to parental need or the ability of the child to give.
Keywords: J14; J22; 330; Intergenerational transfers; old age support; elderly labor supply; Alterssicherung; Privater Transfer; Arbeitsangebot; Alte Menschen; Indonesien; Entwicklungsländer